Benzidine staining: method to detect neutrophils in whole saliva of patients with renal disease - Cardoso, Estela M. del Luján (2015)
Benzidine staining allows for the quantification of peroxidise positive polymorphonuclear leukocytes in whole saliva from patients with renal disease. This is a practical tool for monitoring oral health in this high risk population.